Inside Out: Jethro, the Midianites and a Biblical Construction of the Outsider - Leveen, Adriane (Journal for the study of the Old Testament, 2010)
Attitudes toward the outsider exist on a continuum in the Hebrew Bible. He or she may be attacked, critiqued, brutalized or praised, respected, and at times intentionally included. The treatment of the Midianites is an interesting case in point because it encompasses both ends of that continuum. The Midianite priest Jethro represents an outsider who is welcomed as a trusted advisor and valued participant. The Midianites as a group represent a sexual and idolatrous threat and are ruthlessly attacked by the Israelites. In this article, a close reading examines how such diametrically opposed views of Jethro and the Midianites are constructed, represented and maintained. Violence does not need to be the inexorable outcome of difference.